MANAGEMENT OF POTATO GROWTH AND DEVELOPMENT USING PHYSIOLOGICALLY ACTIVE SUBSTANCES IN SALINE SOIL CONDITIONS (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
This research paper explores the effects of physiologically active substances on the growth and development of potatoes cultivated in saline soil conditions. Salinity is a significant environmental stressor that adversely affects plant growth, leading to reduced yield and quality. The study aims to evaluate how the application of various physiologically active compounds can mitigate the negative impacts of salinity on potato plants.Experiments were conducted under controlled conditions to assess the physiological responses of potato plants treated with different concentrations of these active substances. Key parameters measured included germination rates, root development, leaf area, and overall plant biomass. The results indicated that the application of physiologically active substances significantly improved the growth metrics of potato plants in saline conditions compared to untreated controls.